ANALISIS KETERKAITAN PDRB, PENDIDIKAN DAN INDEKS PEMBERDAYAAN GENDER TERHADAP KEMISKINAN DI LIMA KABUPATEN JAWA TENGAH - Hapsari, Putri Mei; Devani, Shinta Bella; Aprikania, Siti Herinda Deska; Salsabilah, Aida Fitriyani; Dinandhiya, Sarah Faza (Universitas Jambi, 2025)
This study analyzes the influence of economic growth, education levels, and gender empowerment on poverty levels in five districts in Central Java during the period 2010–2023. Using a multiple linear regression approach with a fixed effect model, the results show that economic growth and education have a negative and significant influence on poverty. This means that increases in regional gross domestic product (PDRB) and average years of schooling contribute significantly to reducing povertylevels in the studied areas. Conversely, gender empowerment does not show a significant impact on poverty reduction, indicating the need to strengthen the implementation of gender policies to achieve greater socio-economic impact. Overall, this model explains most of the variation in poverty levels across regions. This study recommends expanding the variables and approaches, including considering spatial aspects and mixed methods, to provide a more comprehensive understanding of regional poverty dynamics.